Study on Emphasizing the Efficiency of a Cellulosolytic Preparation on the Hydrolyzed Wood Wastes - Ana- Despina Ionescu; Angela Casarica; Roxana - Madalina Stoica; Nicoleta Ene (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
According to the literature data, the cellulose, the most abundant organic molecule on Earth, is found mainly as a structural component of plants and algal cell walls, it is also produced by some animals such as tunicates, and it can be produced also by several bacteria, by a natural pathway or by biotechnology. Due to this situation, there are many studies focused on the use of this kind of renewable source and having as their issues the preparation of different valuable products, such as sugars, ethanol. Different chemicals, the whole yeasts biomass valorization with agricultural applications or for biofuels development. Our issue of this present study was to verify if we can avoid the microbial additional activity during the process, mostly while the conversion starts from some materials already pretreated, such as the paper and cellulose industry’s wastes, by using them as substrate in an optimized culture media formula, for the further yeasts strains development.